Space research : rocket launches and similar experiments at Cape Parry, Northwest Territories : understanding between the United States of America and Canada . - United States. Treaties, etc. Canada, Nov. 24, 1975.; United States. Department of State. ([Washington] : U.S. Dept. of State : for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1976)
Mode of access: Internet.